2018
DOI: 10.1002/etc.4161
|View full text |Cite
|
Sign up to set email alerts
|

Transformation‐dissolution reactions partially explain adverse effects of metallic silver nanoparticles to soil nitrification in different soils

Abstract: Risk assessment of metallic nanoparticles (NPs) is critically affected by the concern that toxicity goes beyond that of the metallic ion. The present study addressed this concern for soils with silver nanoparticles (AgNPs) using the Ag-sensitive nitrification assay. Three agricultural soils (A, B, and C) were spiked with equivalent doses of either AgNP (diameter = 13 nm) or AgNO . Soil solution was isolated and monitored over 97 d with due attention to accurate Ag fractionation at low (∼10 μg L ) Ag concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…These observations also correspond with those in the terrestrial assay of Bollyn et al () with the same test items. In that study, 3 soils were spiked with AgNO 3 or AgNPs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These observations also correspond with those in the terrestrial assay of Bollyn et al () with the same test items. In that study, 3 soils were spiked with AgNO 3 or AgNPs.…”
Section: Discussionsupporting
confidence: 88%
“…Based on preliminary experimentation, filters were conditioned with the solution to be filtered before the actual sample for analysis was taken. Preliminary experimentation showed that the optimal procedure was a single conditioning for the conventionally dissolved Ag fraction, and a double conditioning for the truly dissolved Ag fraction (Bollyn et al 2018). Filtrates were acidified with aqua regia (12% HCl/4% HNO 3 ), and an additional digestion step (2 h of heating at 100 °C on an SCP Science DigiPREP MS heating block) was applied before Ag analysis to optimize Ag recovery.…”
Section: Transformation/dissolution Assay With Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of chlorophyll a and intracellular ROS was also not remarkably influenced by Na 2 MoO 4 (Figure S9b,c). The above results indicated different environmental risks than those derived from released Ag ions from Ag nanoparticles . One study found that the formation of abundant surface defects was beneficial for the antibacterial activity of nanomaterials (e.g., carbon materials and metal nanoparticles) on a Gram-negative bacterium ( E. coli ), and could also strengthen the toxicity of nanomaterials to organisms (RT–W1 cells and embryos) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The Registration, Evaluation, Authorization and Restriction of Chemicals regulation dictates that chemicals and nanoparticles (NPs) sold in the European market in volumes greater than 1 ton per year must be characterized for potential impact on aquatic ecosystems (European Commission 2006). In addition, many researches have indicated that a chemical species in nanoscale could exhibit different bioavailability and toxicity from their bulk forms, such as ions and molecules (Böhme et al 2017;Jiang et al 2017;Bollyn et al 2018;Denluck et al 2018); therefore, it is particularly important to understand the potential environmental implications before scaling up for application. The aim of the present study was to determine whether monoalkyl tin clusters are environmentally friendly materials for largescale use in the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%